Peran Pemuda dalam Penanaman Nilai-Nilai Islam Inklusif pada Siswa Madrasah Aliyah Mambaul Ulum Kabupaten Jember - Mohammad Robith Al Hasany (Nusantara: Jurnal Pendidikan Indonesia, 2022)
The purpose of this study is to examine in depth the study of inclusive Islamic values that are actualized for students at Madrasah Aliyah Mambaul Ulum as an effort to realize the noble values of Islamic education, which includes the integration of Islamic educational values with inclusive Islamic values. which includes the value of openness, the value of tolerance, and the value of equality. This study uses a qualitative method of case study type with the determination of the subject using purposive techniques, participant observation data collection techniques, semi-structured interviews, and documentation. Data analysis researchers used source triangulation techniques and data triangulation techniques according to Miles and Huberman data analysis techniques. The role of the taretan sadere youth is as a mobilizer, tutor, and facilitator in inculcating inclusive Islamic values in Madrasah Aliyah Mambaul Ulum students, Jember Regency by using approaches including: discussion/debate approach; school literacy approach; application of values of mutual respect for differences in beliefs; application of the value of harmony; the value of compassion between fellow religions; and the application of the value of religious freedom between religious communities, in addition to the application of intra-and extra-school cooperation, namely concentrating on relationships (togetherness); fostering positive and active values (awareness of sharing and social sensitivity).